Enriching the knowledge of altmetrics studies by exploring social media metrics for Economic and Business Studies journals - Kaltrina Nuredini; Isabella Peters (Proceedings of the 21st International Conference on Science and Technology Indicators (STI Conference 2016), València (Spain), September 14-16, 2016, 2016)
We present a case study of articles published in 30 journals from Economics and Business Studies (EBS) by using social media metrics from Altmetric.com. Our results confirm that altmetric information is significantly better present for recent articles. The Top 3 most used altmetric sources in EBS-journals are Mendeley, Twitter, and News. Low but positive correlations (r=0.2991) are identified between citation counts and Altmetric Scores on article level but they increase on journal level (r=0.614). However, articles from highly cited journals do neither receive high online attention nor are they better represented on social media.
Keywords: 330; altmetrics